Biodiversity Gradients: Is Diversity Greater in the Tropics? - Kowalczyk, Karolina; Uchmański, Janusz (Studia Ecologiae et Bioethicae, 2025)
This paper examines hypotheses explaining greater biodiversity in the tropics compared to regions located at higher latitudes. The results of studies of the biodiversity of different groups of organisms along latitudinal transects are presented to demonstrate the existence of latitudinal gradients of biodiversity. Hypotheses explaining the existence of regular gradients of biodiversity, i.e. such changes in biodiversity when it increases with approaching the equator: uneven distribution of the sizes of the tropics and temperate zones, the so-called middle domain effect, uneven latitudinal distribution of energy reaching the Earth’s surface and other evolutionary and ecological hypotheses. Moreover, explanations for reverse gradients of biodiversity are discussed. Attention is drawn to the different nature of the conditions for these explanations and to the rather large gaps in data that could be useful to resolve these issues.